VULNUS LACERATUM TREATMENT IN A LOCAL DOG: A CASE REPORT - Keliat, Dosmonytha Br; Wirata, I Wayan; Pemayun, I Gusti Agung Gde Putra (Buletin Veteriner Udayana, 2026)
Vulnus laceratum is a lacerated wound with an irregular shape caused by either sharp or blunt objects that penetrate the skin or underlying muscle. A three-year-old white dog named Snowi, weighing 24 kg, presented with an open wound near the base of the penis, which had become infected after repeated scratching over the past three weeks. Based on the history and observed clinical signs, the dog was diagnosed with vulnus laceratum at the base of the penis, with a favorable prognosis (fausta). Surgical management was performed according to standard wound care principles, including wound cleansing, removal of necrotic or damaged tissue (debridement), and wound closure using sutures. Postoperative treatment included administration of cefotaxime at a dose of 10 mg/kg, cefixime twice daily for seven days, and topical application of iodine to the sutured wound. By day nine, the wound had dried and the sutures were removed. The treatment in this case proved effective, as complete healing was achieved by the ninth day. The owner is advised to provide better care both during the postoperative period and afterward to prevent recurrence of similar lacerated wounds.